On the Comparison of Public Health and Social Support in Addicts and Non-Addicts - touraj hashemi; yones gasembaklo; reza mohammadzadeghan; sajjad vakili; mohammadamin irani (Drug Control Headquarters, Research and Education Office, 2015)
Objective: This study aimed at comparing the degree of public health and social support in addicted and non-addicted people. Method: This study was causative-comparative and all addicts who had referred to addiction treatment centers in city of Khoy in 2012 constituted its population. From among this population, 60 addicts through convenience sampling method were selected and then peered with 60 normal subjects by age, gender, and education. The measurement tools were Goldberg Public Health (Ghq-28) and Social Support (Fleming) questionnaires. Results: The results showed That Addicts enjoy a lower degree of Mental Health and Social Support. Conclusion: Providing social support for the addicts under treatment programs is one of the important factors in withdrawal from drug use.